Comparison of vocal outcomes after angiolytic laser surgery and microflap surgery for vocal polyps. Issue 6 (December 2015) - Mizuta, Masanobu; Hiwatashi, Nao; Kobayashi, Toshiki; Kaneko, Mami; Tateya, Ichiro; Hirano, Shigeru
Abstract Objective The microflap technique is a standard procedure for the treatment of vocal fold polyps. Angiolytic laser surgery carried out under topical anesthesia is an alternative method for vocal polyp removal. However, it is not clear whether angiolytic laser surgery has the same effects on vocal outcomes as the microflap technique because of a lack of studies comparing both procedures. In the current study, vocal outcomes after both procedures were compared to clarify the effects of angiolytic laser surgery for vocal polyp removal. Methods Vocal outcomes were reviewed for patients who underwent angiolytic laser surgery (n = 20, laser group) or microflap surgery (n = 34, microflap group) for vocal polyp removal. The data analyzed included patient and lesion characteristics, number of surgeries required for complete resolution, and aerodynamic and acoustic examinations before and after surgery. Results In the laser surgery group, complete resolution of the lesion was achieved with a single procedure in 17 cases (85%) and with two procedures in 3 cases (15%). Postoperative aerodynamic and acoustic parameters demonstrated significant improvement compared to preoperative parameters in both the laser surgery group and the microflap surgery group. There were no significant differences in any postoperative aerodynamic and acoustic parameters between the two groups. Conclusion The current retrospective study demonstrated that angiolytic laser surgery achieved complete resolution of vocal polyps within two procedures. Postoperative effects on aerodynamic and acoustic functions were similar to those after microflap surgery.